(untitled) (Libya Journal of Geographical Studies, 2024)
This study aims to analyze the morphometric characteristics of the Wadi El Hanawi Basin using Geographical Information System (GIS), based on the Digital Elevation Model (DEM) with a discriminatory accuracy of 12 meters, to identify and extract the drainage network and classify its ranks according to the classification (Strahler, 1957), Mathematical equations were also used to calculate the values ​​of many variables, which include areal morphometric characteristics, topographic characteristics, in addition to the characteristics of the water drainage network. The study was divided into four axes, where the first axis includes the theoretical framework of the study, the second axis the natural characteristics, and the third axis deals with the analysis of Morphometric characteristics of the Wadi El Hanawi Basin, while the fourth axis included results and recommendations. The study concluded that the Wadi Basin reached the sixth rank with a number of 2,472 streams, and the first and second class streams constitute more than 97% of the number of streams, with low drainage density, in addition to establishing a database. The morphometric characteristics of the Wadi El Hanawi Basin can be used in water resources studies and management.